Enteroátógenos con potencial zoonótico en felinos clínicamente sanos: Implicaciones en la salud pública (2021)
Domestic animals such as cats harbor many pathogens capable of infecting humans, transmitted through their feces by direct and indirect contact, the latter being transmitted by contact with contaminated soil, soil, water and food. The objective of this work was to carry out a review of the main enteropathogens with zoonotic potential in clinically healthy felines and their implications for public health at the national and international context. As a result of the exhaustive literature search on the subject and taking into account the report of the Subdirectorate of Surveillance and Control in Public Health (SIVIGILA), it was found that the main zoonotic enteropathogens in cats are Escherichia coli, Salmonella spp, Shigella spp, Campylobacter spp and Clostridium spp, but despite this they are not on the SIVIGILA list and, therefore, the pertinent measures are not taken for the prevention of said diseases transmitted by them